PERAN GURU DALAM PROSES PENGEMBANGAN KURIKULUM PAI - Trysha Yulindaputri; Tasman Hamami (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The curriculum must be dynamic in nature that adapts to the changes and developments of the times, science and the needs of society. The curriculum development process includes three stages, namely: planning, implementation, and evaluation. Teachers have an important role in the curriculum development process. But in reality, teachers lack awareness and ability, so their participation is low in curriculum development. This study aims to analyze the role of teachers in the PAI curriculum development process. The research approach used is library research, which seeks materials collected from books and scientific publications that are relevant to the topic discussed. The results showed that curriculum development includes planning, implementation and evaluation. In curriculum development, some of the roles of teachers are as implementers, implementing the curriculum that has been determined; as adapters, adjusting the curriculum; as developers, modify the curriculum according to the characteristics of the school and the needs of students; as researchers, testing various curriculum components.